2023
DOI: 10.1177/10600280231171373
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Kidney Injury Based on Vancomycin Target Trough Attainment Strategy: Area-Under-the-Curve-Guided Bayesian Software, Nomogram, or Trough-Guided Dosing

Abstract: Background: Guidelines support area-under-the-curve (AUC) monitoring for vancomycin dosing which may lower overall doses and reduce acute kidney injury (AKI). Objective: The aim of this study was to compare incidence of AKI across 3 vancomycin dosing modalities: AUC-targeted Bayesian pharmacokinetic software, AUC-targeted empiric dosing nomogram, and trough-guided dosing using clinical pharmacists’ judgment. Methods: This retrospective study included adult patients with a pharmacy dosing consult who received ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Another recent retrospective study found a reduction in AKI with Bayesiandosed vancomycin compared with trough-guided dosing (aOR = 0.72, 95% CI = 0.58-0.89), though similar rates of AKI were seen when comparing Bayesian dosing with an AUC nomogram dosing strategy. 16 There are a few reasons why MIPD/Bayesian dosing may have resulted in a reduced incidence of AKI for patients on VPT within our study. The Bayesian dosing software provides several different models, including one for obese patients which was utilized for some of the included patients in this study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another recent retrospective study found a reduction in AKI with Bayesiandosed vancomycin compared with trough-guided dosing (aOR = 0.72, 95% CI = 0.58-0.89), though similar rates of AKI were seen when comparing Bayesian dosing with an AUC nomogram dosing strategy. 16 There are a few reasons why MIPD/Bayesian dosing may have resulted in a reduced incidence of AKI for patients on VPT within our study. The Bayesian dosing software provides several different models, including one for obese patients which was utilized for some of the included patients in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Another recent retrospective study found a reduction in AKI with Bayesian-dosed vancomycin compared with trough-guided dosing (aOR = 0.72, 95% CI = 0.58-0.89), though similar rates of AKI were seen when comparing Bayesian dosing with an AUC nomogram dosing strategy. 16…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pharmacists have further demonstrated their contribution to patients recovering from an AKI episode by establishing post-discharge follow-up services [ 36 , 37 ]. Pharmacists play also a crucial role in AKI prevention by monitoring nephrotoxic drug levels [ 38 ], although some studies present conflicting conclusions [ 39 ]. Initial results from a large randomized controlled trial revealed that pharmacists, as part of a trained multidisciplinary team, adjusted doses, or initiated drug level monitoring in nearly 70% of patients with AKI [ 40 ].…”
Section: Discussionmentioning
confidence: 99%